2009
DOI: 10.1007/s00244-009-9380-1
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Biomarkers in the Digestive Gland of Theba pisana Exposed to Heavy Metals

Abstract: The in vivo toxic effects of sublethal treatment of 40 and 80% of 48-h LD(50) of topically applied trace metals [copper (Cu), lead (Pb), and zinc (Zn)] on oxidative stress biomarkers in the digestive gland of Theba pisana were examined. Oxidative individual perturbations were assessed by measuring nonenzymatic (glutathione; GSH) and enzymatic (catalase, CAT; glutathione peroxidase, GPx; and glutathione-S-transferase, GST) antioxidants in digestive gland of the snails. Lipid peroxidation (LPO) was also evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 41 publications
4
22
1
Order By: Relevance
“…Consequently, the CAT antioxidant is a very important component of intracellular antioxidant defense system in organisms, because it reduces H 2 O 2 and oxygen to prevent oxidative stress [36], [40]. Radwan, et al reported significant CAT activity increase in Theba pisana exposed to trace metals (Cu, Pb and Zn) after 48h, and they suggested this increase in antioxidant defenses may protect the cells from damage, maintaining cell homeostasis [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the CAT antioxidant is a very important component of intracellular antioxidant defense system in organisms, because it reduces H 2 O 2 and oxygen to prevent oxidative stress [36], [40]. Radwan, et al reported significant CAT activity increase in Theba pisana exposed to trace metals (Cu, Pb and Zn) after 48h, and they suggested this increase in antioxidant defenses may protect the cells from damage, maintaining cell homeostasis [3].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, heavy metal is considered to be one of the most important contamination sources strongly affecting fish population, growth and reproduction [2]. Instead of atmospheric sources, heavy metals often enter the environment mainly through human activities circulate in food webs and accumulate in living organisms [3]. Non-essential heavy metals are harmful and sometimes even lethal toxins that may lead to fertility decline, cellular damage, cell death and dysfunction of a variety of organs when accumulated in tissues [4].…”
Section: Introductionmentioning
confidence: 99%
“…Cell apoptosis was induced by stress, such as free radicals, hypoxia and blood deficiency (20,21). The present study focused on the function of Bcl2 and Bax in the regulation of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The induction of oxidative stress in biological systems by lead is reported by several researchers however, mechanism of ROS induction is unknown [18]- [20]. The actual mechanism of elimination of ROS like superoxide anion radical is generally by the dismutation activity of SOD producing hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%